The impact of COVID-19 social restrictions on culture and psychosocial well-being: The Ghanaian experience - Dai-Kosi, A.D.; Acquaye, V.A.; Pereko, K.K.A.; et al. (Mental Health Effects of COVID-19, 2021)
In December 2019 what began as local transmission of a novel coronavirus disease in the Wuhan Province of China escalated into a global pandemic as declared by the World Health Organization (WHO). The first reported case of Coronavirus (COVID-19) in Ghana was recorded on 12th March 2020 when two persons tested positive for the virus (MoH, 2020). As of 16th July 2020, the disease had spread exponentially to a new global record of 13,378, 853 cases with 580,045 deaths. In Ghana, as of the same 16th July 2020, 26,125 persons were infected while 139 had lost their lives (WHO, 2020). This chapter looks at the concept of COVID-19 lockdown and restrictions especially their influence on the sociocultural life of Ghanaians. It also evaluates the impacts of corona runs on individuals about social support in a highly communal society. In addition, the chapter reviews the health beliefs and health-seeking attitudes of the people of Ghana considering the threat of coronavirus. Finally, it proffers strategies to help bring coronavirus under control while the people go about their daily activities.
Research Article
Keywords: impact of COVID-19; social restrictions; psychosocial well-being